Autophosphorylation at serine 166 regulates RIP kinase 1-mediated cell death and inflammation - Lucie Laurien (Nature Portfolio, 2020)
Receptor interacting protein kinase 1 (RIPK1) regulates cell death and inflammatory responses. Here the authors show that autophosphorylation at Ser166 is required for RIPK1-mediated cell death and inflammation in mouse models of inflammatory pathologies, making Ser166 phosphorylation a possible biomarker for RIPK1-mediated inflammatory diseases.